Persepsi Mahasiswa Jurusan Pariwisata Budaya Terhadap Twitter Sebagai Sarana Pembelajaran Kosakata Bahasa Inggris - Md. Yudyantara Risadi; Ni Luh Putu Uttari Premananda; Ni Made Rai Kristina (Tampung Penyang, 2022)
This study aimed at finding out the perception of students in tourism program towards Twitter as vocabulary learning media. Twitter has become one of the learning media in this 4.0 era. It is undeniable that Twitter existence becomes one of the social media that students choose to use when they are learning english subject material. This situation can be used by the teacher to have a specific learning technique when teaching the students about vocabulary via social media especially Twitter. The teachnique used in this study was survey in which all students become the sample of this study considering that all the students have access to Twitter. Survey was conducted by using questionnaire with 15 statements to gain their perception towards Twitter,. Then the data was processed in order to gain the result in the form of percentage. From